Legal Accountability of Officials and Police For Damage or Loss of Seized Goods - Ade Papa Rihi; Zudan Arief Fakrulloh (Syntax Corporation Indonesia, 2024)
This research discusses the legal vacuum regarding the accountability of law enforcement officials, specifically the police, in the management of seized goods that have experienced damage or loss. The main focus of this research is to identify weaknesses in existing regulations and their impact on legal certainty and the protection of the rights of the owners of the goods. By analyzing the ambiguities in the laws and examining real case studies, this research finds that the legal vacuum leads to material losses for the owners and decreases public trust in law enforcement agencies. As a solution, the research recommends legal reforms through the establishment of clearer regulations regarding the obligations of seized goods managers to provide compensation, as well as strengthening administrative procedures and strict monitoring to create a fair and transparent legal system